Conspiracy Theories : Secrecy and Power in American Culture - Fenster, Mark (Book collections on Project MUSE., 2008)
JFK, Karl Marx, the Pope, Aristotle Onassis, Queen Elizabeth II, Howard Hughes, Fox Mulder, Bill Clinton-all have been linked to vastly complicated global (or even galactic) intrigues. In this enlightening tour of conspiracy theories, Mark Fenster guides readers through this shadowy world and analyzes its complex role in American culture and politics. Fenster argues that conspiracy theories are a form of popular political interpretation and contends that understanding how they circulate through mass culture helps us better understand our society as a whole. To that end, he discusses Richard Ho.